The Impact of Artificial intelligence on fraud detection in Digital Banking: An Empirical study - Kanika Mittal, Shweta Ahuja (Journal of Informatics Education and Research, 2025)
Artificial intelligence (AI) is an emerging technology that transforms the fundamental principles of digital banking. One of the key implementations in banking and finance is fraud detection, which has proven necessary because cyber-attacks are as frequent and creative these days. This paper is an empirical investigation of AI's effect on fraud detection used by digital banking. The re- search evaluates the ability of different artificial intelligence (AI) methods like machine learning and natural language processing to identify fraud cases. AI has proved to enhance the accuracy and agility of fraud detection in digital banking; therefore, with its assistance, customers' financial assets are more protected than ever, and the results speak for themselves. This quantitative study will collect data from digital banking platforms concerning the prevalence of fraud detection through AI. We will back this up by talking to fraud management experts about their experience and opinions on using AI in fraud detection. This study's find- ings hope to demonstrate that AI impacts fraud detection within digital banking and, thus, its ability to increase the security and confidence of customers within a digital banking environment. The present study intends to evaluate the current understanding of different factors that implementation functions. Results from the work can aid the banking sector in developing and enhancing AI-fueled fraud detection models, thus leading to a fail-proof experience for customers as banks offer them a risk-free digital banking journey.